1997
DOI: 10.1126/science.277.5332.1625
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Emissions from Comets Detected in the Röntgen X-ray Satellite All-Sky Survey

Abstract: After the unexpected discovery of x-rays emitted from comet C/1996 B2 (Hyakutake) with the Röntgen X-ray Satellite (ROSAT) in March 1996, x-ray emissions from comets C/1990 K1 (Levy), C/1990 N1 (Tsuchiya-Kiuchi), 45P (Honda–Mrkos–Pajdušáková), and C/1991 A2 (Arai), optically 300 to 30,000 times fainter than Hyakutake, were discovered in archival ROSAT data. These findings establish comets as a class of x-ray sources and allow their properties to be studied over a wide optical brightness range. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 13 publications
6
116
2
Order By: Relevance
“…For comets, due to very large spatial scales of the neutral gas distribution, the heavy ion component of the solar wind is totally depleted while moving through the cometary coma (that is the reason of the absent of the X-ray emission from the tail) and the peak X-ray flux is determined by the heavy ion density [Dennerl et al, 1997].…”
Section: Implications For Remote Sensingmentioning
confidence: 99%
“…For comets, due to very large spatial scales of the neutral gas distribution, the heavy ion component of the solar wind is totally depleted while moving through the cometary coma (that is the reason of the absent of the X-ray emission from the tail) and the peak X-ray flux is determined by the heavy ion density [Dennerl et al, 1997].…”
Section: Implications For Remote Sensingmentioning
confidence: 99%
“…Finally, in section 5 we present a comparison of the different theoretical models together with observations of X ray emission from comet P/Hyakutake [Lisse et al, 1996] and other cometary sources from the ROSAT archive [Dennerl et al, 1997] and Beppo-SAX measurements of X ray emission from comet P/Hale-Bopp [Owens et al, 19981 . The serious contradictions existing between the charge exchange model and the observations indicate that the charge exchange mechanism cannot be the sole mechanism responsible for the X ray emission; radiation produced by energetic electron impacts with the cometaw neutrals can also be important. Our analysis demonstrates good agreement between a model of radiation produced by energetic electrons and observations of the spectrum of the X ray emission and the size and position of the emitting area.…”
mentioning
confidence: 99%
“…Of the several possible excitation mechanisms (Wickramasinghe & Hoyle 1996;Cravens 1997;Bingham et al 1997Bingham et al , 2000Northrop et al 1997;Ip & Chow 1997;Uchida et al 1998;Shapiro et al 1999), the charge transfer of solar wind ions in collisions with the cometary atmosphere (Cravens 1997) appears to be the most plausible (Häberli et al 1997;Mumma et al 1997;Wegmann et al 1998;Kharchenko & Dalgarno 2000;Schwadron & Cravens 2000). If the charge transfer mechanism dominates the excitation, then with sufficient spectral resolution the composition of the solar wind can be inferred from a comparison of the observed spectra with the spectra predicted from charge transfer (Dennerl et al 1997;Kharchenko & Dalgarno 2000;Schwadron & Cravens 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They incorporate the contributions from the impacts of the fast solar wind and the slow solar wind that have different ion compositions. From a comparison with the observational data (Dennerl et al 1997), Schwadron & Cravens (2000) concluded that comet C/1990 K1 (Levy) was subjected primarily to the fast solar wind. We employ a more detailed description of the capture and radiative processes and argue that X-ray emissions from comets C/1990 K1 (Levy), P/Encke 1997, and C/1995 O1 (Hale-Bopp) were induced by slow wind ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation